Importance of tissue culture for orphan crops - Dubois, T. (2010)
Tissue culture is one of the most basic biotechnological tools available in sub-Saharan Africa (SSA), and its applications are varied and vast. The technique has contributed tremendously to the safeguarding, improvement and distribution of orphan crops, especially the vegetatively produced crops. As a tool, it has been a driver for biotechnological advances made in orphan crops, both for research as well as commercial purposes. Tissue culture is also a vehicle to most efficiently deliver important biotechnological products such as genetically modified orphan crops. Commercial micropropagation, despite potential pitfalls, is essential tool to distribute crops such as cassava and banana to smallholder farmers in SSA.